The complete package [refurbished computers, Kenya] - Okono, Fred (Technical Centre for Agricultural and Rural Cooperation, 2007)
Giving young people access to technology has to involve more than giving away old computers. For one Kenyan organization it is also about training, partnerships and policy change.